2022
DOI: 10.1002/for.2904
|View full text |Cite
|
Sign up to set email alerts
|

Geopolitical risk and global financial cycle: Some forecasting experiments

Abstract: In this study, we investigate the connection between geopolitical risk (GPR) and global financial cycle (GFCy) as well as whether the former has predictive value for the out‐of‐sample predictability of the latter. We utilize both the historical and recent GPR data and their variants, namely, GPR act covering all “acts” that constitute GPR such as war, nuclear invasion and terrorism, and GPR threat, which represents threats of these acts. We construct a predictive model that accommodates the salient features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Shaik et al (2023) showed that GPR affected stock, gold, and oil returns during the disruptive events of the worldwide economic downturn, COVID-19, and the 2022 Russia-Ukraine war [37]. Salisu et al (2023) emphasized the predictive value of GPR in the global financial cycle (GFCy) [38]. Li et al (2023) found that GPR affects the cost of natural resources, which are necessary for a healthy economy and way of life [39].…”
Section: Literaturementioning
confidence: 99%
“…Shaik et al (2023) showed that GPR affected stock, gold, and oil returns during the disruptive events of the worldwide economic downturn, COVID-19, and the 2022 Russia-Ukraine war [37]. Salisu et al (2023) emphasized the predictive value of GPR in the global financial cycle (GFCy) [38]. Li et al (2023) found that GPR affects the cost of natural resources, which are necessary for a healthy economy and way of life [39].…”
Section: Literaturementioning
confidence: 99%